Multi year aerosol characterization in the tropical Andes and in adjacent Amazonia using AERONET measurements. (October 2017) - Pérez-Ramírez, Daniel; Andrade-Flores, Marcos; Eck, Thomas F.; Stein, Ariel F.; O'Neill, Norman T.; Lyamani, Hassan; Gassó, Santiago; Whiteman, David N.; Veselovskii, Igor; Velarde, Fernando; Alados-Arboledas, L.
Abstract: This work focuses on the analysis of columnar aerosol properties in the complex geophysical tropical region of South America within 10–20° South and 50–70° West. The region is quite varied and encompasses a significant part of Amazonia (lowlands) as well as high mountains in the Andes (highlands, ∼4000 m a.s.l.). Several AERONET stations were included to study the aerosol optical characteristics of the lowlands (Rio Branco, Ji Parana and Cuiaba in Brazil and Santa Cruz in Bolivia) and the highlands (La Paz, Bolivia) during the 2000–2014 period. Biomass-burning is by far the most important source of aerosol in the lowlands, particularly during the dry season (August–October). Multi-annual variability was investigated and showed very strong burning activity in 2005, 2006, 2007 and 2010. This resulted in smoke characterized by correspondingly strong, above-average AODs (aerosol optical depths) and homogeneous single scattering albedo (SSA) across all the stations (∼0.93). For other years, however, SSA differences arise between the northern stations (Rio Branco and Ji Parana) with SSAs of ∼0.95 and the southern stations (Cuiaba and Santa Cruz) with lower SSAs of ∼0.85. Such differences are explained by the different types of vegetation burned in the two different regions. In the highlands, however, the transport of biomass burning smoke is found to be sporadic in nature. This sporadicity results in highly variable indicators of aerosol load and type (Angstrom exponent and fine mode fraction) with moderately significant increases in both. Regional dust and local pollution are the background aerosol in this highland region, whose elevation places it close to the free troposphere. Transported smoke particles were generally found to be more optical absorbing than in the lowlands: the hypothesis to explain this is the significantly higher amount of water vapor in Amazonia relative to the high mountain areas. The air-mass transport to La Paz was investigated using the HYSPLIT air-concentration five-days back trajectories. Two different patterns were clearly differentiated: westerly winds from the Pacific that clean the atmosphere and easterly winds favoring the transport of particles from Amazonia. Highlights: Aerosol in the Bolivian Andes. Aerosol transport to high mountains. Biomass-burning near the Andes.